Measurement of total blood flow in the normal human retina using Doppler Fourier-domain optical coherence tomography - Wang, Y (2009)
AIM: To measure total retinal blood flow in normal human eyes using Doppler Fourier-domain optical coherence tomography (FD-OCT). METHODS: 10 normal people aged 35 to 69 years were measured for the right eye using Doppler FD-OCT. Double circular scans around the optic nerve heads were used. Four pairs of circular scans that transected all retinal branch vessels were completed in 2 s. Total retinal blood flow was obtained by summing the flows in the branch veins. Measurements from the eight scans were averaged. Veins with diameters >33 μm were taken into account. RESULTS: Total retinal blood flow could be measured in eight of 10 subjects: mean (SD) = 45.6 (3.8) μl/min (range 40.8 to 52.9 μl/min). The coefficient of variation for repeated measurements was 10.5%. Measured vein diameters ranged from 33.3 to 155.4 μm. The averaged flow speed was 19.3 (2.9) mm/s, which did not correlate with vessel diameter. There was no significant difference between flows in the superior and inferior retinal hemispheres. CONCLUSIONS: Double circular scanning using Doppler FD-OCT is a rapid and reproducible method to measure total retinal blood flow. These flow values are within the range previously established by laser Doppler flowmetry.